Direct AMS 14C Analysis of Carbonate. Issue 5 (October 2019) - Hua, Quan; Levchenko, Vladimir A; Kosnik, Matthew A
ABSTRACT: We have investigated the possibility of direct accelerator mass spectrometry radiocarbon (AMS 14 C) measurement of carbonate samples at ANSTO using the STAR 2 MV tandem accelerator. Each carbonate sample was powdered, mixed with metal powder and pressed into an aluminum cathode for direct carbonate measurement by AMS 14 C. Of the three high-purity metal powders (Fe, Nb, and Ag) used in our investigation, Nb was found to be the best metal, which delivered higher carbon beam currents and lower background. Beam currents for targets containing the optimal carbonate mass of 1.5–2.0 mg were ∼8% of those obtained from graphite targets of standard size (>0.5 mg C). Typical measured blank for Carrara marble (IAEA-C1) of ∼40 ka was obtained. Background-corrected 14 C values of carbonate targets agreed well with their associated values obtained from high-precision analysis of graphite targets within 2σ uncertainties. Typical precision of this rapid AMS analysis was ∼1% for samples <8 ka. Despite lower precision for carbonate target ages (compared to standard graphite target ages), these ages are useful for palaeobiological applications where a large number of dates are required, such as time-averaging studies.